Association between quality performance scorecard scores and health indicators: an ecological study in the Northern provinces of the Lao People’s Democratic Republic - Vixayyang Chayvangmanh; Noudéhouénou Credo Adelphe Ahissou; Khamsay Detleuxay; Daisuke Nonaka (Tropical Medicine and Health)
Abstract Background The Ministry of Health, Lao People's Democratic Republic (Lao PDR), surveyed health centers using the Quality Performance Scorecard (QPS) tool in 2021 to assess the quality of healthcare services at health centers. To validate the QPS tool, this study assessed the association between the QPS scores obtained from each health center and outpatient department (OPD) visits, antenatal care (ANC) coverages, and under-five mortality rates (U5MR) in the health centers' catchment area. Methods This ecological study assessed the association between the QPS scores as an independent variable and OPD visits, coverage of ANC at least one visit (ANC1), coverage of ANC four or more visits (ANC4) and U5MR as a dependent variable, using secondary data collected from the 234 health centers and 31 district health offices in the four northern provinces, such as Huaphan, Xiengkhuang, Oudomxay and Phongsaly. Mixed-effect linear regression was used to assess the association between the independent variable and dependent variables while adjusting for covariates. Results The mean value (standard deviation) was 64.9/100 (14.3) for QPS score, 3.3 (3.6) for U5MR (per 1,000 under-five population), 0.7 (0.5) for OPD visits (per population), 9.6 (6.0) for ANC1 coverage (per estimated number of reproductive-aged women) and 5.7 (4.4) for ANC4 coverage. The QPS scores were significantly independently associated with U5MR (unstandardized regression coefficient: −0.225 and standardized regression coefficient: −0.894), OPD visits (−0.004 and −0.114) and ANC4 coverage (−0.036 and −0.117). Conclusion This study shows that with increasing level of quality of healthcare services as measured by QPS, the U5MR was decreasing. The association demonstrated the ability of the QPS tool to capture the quality of healthcare services at health centers. Although the QPS scores were also negatively associated with OPD visits and ANC4 coverage, these associations were weak and likely confounded by unmeasured factors, or explained by quality care potentially reducing patients’ perceived need for frequents visits. To further validate the QPS tool, a longitudinal study is recommended to confirm the findings and address unmeasured factors.